The use of acute normovolemic hemodilution in paediatric cardiac surgery. Issue 6 (4th March 2018) - Crescini, W. M.; Muralidaran, A.; Shen, I.; LeBlanc, A.; You, J.; Giacomuzzi, C.; Treggiari, M. M.
Abstract : Background: Acute normovolemic hemodilution (ANH) is considered safe and effective in decreasing perioperative transfusion in paediatric populations undergoing high blood‐loss surgeries. We determined the association between ANH and the intraoperative use of allogeneic blood products in paediatric cardiac surgery patients. Methods: This is a single‐centre retrospective cohort study including paediatric patients between 0 and 36 months of age undergoing surgical repair or palliation of their cardiac defect with the use of cardiopulmonary bypass between November 2013 and November 2014. Our primary endpoint was the volume per kilogram of body weight of any blood product administered. Secondary endpoints were postoperative bleeding, coagulation profile, creatinine, vasoactive support, duration of mechanical ventilation, and hospital stay. Results: In all, 50 patients met eligibility criteria and were included. Of those, seven were exposed to ANH and while 43 patients were treated according to usual care. Baseline characteristics were similar in both groups. After adjustment for baseline characteristics including age, American Society of Anaesthesiologists (ASA) classification, and Risk Adjusted Congenital Heart Surgery score, ANH was associated with reduced administration of allogenic blood products, with the mean difference between groups of 57.5 ml/kg (95% CI: 34.8, 80.2). The ANH group had lower blood losses at 6 and 24 h postoperatively. There were no differences in the duration of ICU or hospital stay. Conclusion: We found a reduction in the administration of blood products and lower postoperative blood losses associated with the use of ANH in paediatric cardiac surgery patients. The data suggest that ANH might be beneficial in reducing perioperative morbidity in this patient population.